2022
DOI: 10.1180/mgm.2022.54
|View full text |Cite
|
Sign up to set email alerts
|

Uvite, CaMg3(Al5Mg)(Si6O18)(BO3)3(OH)3(OH), a new, but long-anticipated mineral species of the tourmaline supergroup from San Piero in Campo, Elba Island, Italy

Abstract: Uvite, CaMg3(Al5Mg)(Si6O18)(BO3)3(OH)3(OH), is a new mineral of the tourmaline supergroup. It occurs in the Facciatoia quarry, San Piero in Campo, Elba Island, Italy (42°45′04.55″N, 10°12′50.89″E) at the centre of a narrow (2–3 cm wide) vein composed of aggregates of dark brown to black tourmaline, penetrating (magnesite + dolomite)-rich hydrothermally altered metaserpentinite. Crystals are euhedral and up to 1 cm in size, brown with a vitreous lustre, conchoidal fracture and grey streak. Uvite has a Mohs hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Nickel-and Fe 3+ -rich oxy-dravite from the Artana Mn prospect (Apuan Alps) is the fourth well-characterized non-pegmatitic tourmaline supergroup minerals from Tuscany. Along with the recently approved new minerals dutrowite (Biagioni et al 2020), uvite (Bosi et al 2022b), and magnesio-lucchesiite (Scribner et al 2021), it suggests that further crystal-chemical investigations on the many tourmaline occurrences from this Italian sector may be able to improve the tourmaline systematics and our understanding of its crystal chemistry. Moreover, the studied sample is one of the Ni-richest so far described and it occurs in a different geological setting concerning the previously-known occurrences for Ni-bearing tourmalines.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nickel-and Fe 3+ -rich oxy-dravite from the Artana Mn prospect (Apuan Alps) is the fourth well-characterized non-pegmatitic tourmaline supergroup minerals from Tuscany. Along with the recently approved new minerals dutrowite (Biagioni et al 2020), uvite (Bosi et al 2022b), and magnesio-lucchesiite (Scribner et al 2021), it suggests that further crystal-chemical investigations on the many tourmaline occurrences from this Italian sector may be able to improve the tourmaline systematics and our understanding of its crystal chemistry. Moreover, the studied sample is one of the Ni-richest so far described and it occurs in a different geological setting concerning the previously-known occurrences for Ni-bearing tourmalines.…”
Section: Discussionmentioning
confidence: 94%
“…Three additional species have been discovered during the crystal-chemical characterization of non-pegmatitic tourmalines from Tuscany. Uvite and magnesio-lucchesiite were identified in veins within metabasite of the thermal aureole of the Monte Capanne intrusion (Bosi et al 2022b;Scribner et al 2021), whereas dutrowite was taining sub-millimetric prismatic crystals of a potential tourmaline supergroup mineral was identified. The mineralogical study confirmed the first identification, pointing out a high Ni content and suggesting the necessity of its full crystal-chemical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Texture effects were corrected using spherical harmonics (8th-order, nine refinable parameters), selecting the number of appropriate terms by using the approach of Ballirano (2003). Starting structural data were taken from Bosi et al (2022) and each refined structure at a given non-ambient T was used as input for the subsequent T. Experimental conditions and miscellaneous information regarding the refinements are listed in Table 1, a magnified 3D-plot of the full data set is shown in Fig. 1, and a representative example of Rietveld plots is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of Ca-rich tourmalines in nature was experimentally demonstrated to be a function of pressure, temperature and metamorphic fluids composition (Berryman et al 2016), but calcic tourmalines remain so far the less investigated in terms of thermal behaviour, dehydration and breakdown products, also because uvite, ideally CaMg 3 (Al 5 Mg)(Si 6 O 18 ) (BO 3 ) 3 (OH) 3 (OH), was only recently officially approved by the International Mineralogical Association's Commission on Nomenclature and Classification as a new mineral species of tourmaline supergroup (Bosi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Occupancies of octahedral sites were refined using bond-valence optimisation (Table 3) which confirmed disorder of Mg and Al between the Y- and Z-sites, typical for Mg-rich tourmalines (e.g. Grice and Ercit, 1993; Hawthorne et al , 1993; Ertl et al , 2003; Bosi and Lucchesi, 2004; Bosi and Skogby, 2013; Bačík, 2015; Pieczka et al , 2018; Scribner et al , 2021; Bosi et al , 2022; Sȩk et al , 2022).…”
Section: Crystal Structure and Bond Valence Refinementmentioning
confidence: 96%